Предмет: Алгебра,
автор: кисуня4
Очень нужно решение! Пожалуйста
Приложения:
![](https://files.topotvet.com/i/f95/f95b8137818fa2a6fe00214bd3153954.jpg)
Ответы
Автор ответа:
0
( x^2 + 3x)^2 + (x^2 + 3x) = 6
x^4 + 6x^3 + 9x^2 + x^2 + 3x - 6 = 0
x^4 + 6x^3 + 10x^2 + 3x - 6 = 0
( x^2 + 3x - 2)(x^2 + 3x + 3) = -
x^2 + 3x - 2 = 0
D = b^2 - 4ac = 9 + 8 = 17
x1,2 = ( - 3 +/-√17) / 2
x^2 + 3x + 3 = 0
D = b^2 - 4ac = 9 - 12 = - 3 - корней нет,так как D - отрицательный.
x1*x2 = (-3+√17)/2 * (- 3-√17)/2 = (9 - 17)/4 = - 8/4 = - 2
x^4 + 6x^3 + 9x^2 + x^2 + 3x - 6 = 0
x^4 + 6x^3 + 10x^2 + 3x - 6 = 0
( x^2 + 3x - 2)(x^2 + 3x + 3) = -
x^2 + 3x - 2 = 0
D = b^2 - 4ac = 9 + 8 = 17
x1,2 = ( - 3 +/-√17) / 2
x^2 + 3x + 3 = 0
D = b^2 - 4ac = 9 - 12 = - 3 - корней нет,так как D - отрицательный.
x1*x2 = (-3+√17)/2 * (- 3-√17)/2 = (9 - 17)/4 = - 8/4 = - 2
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Физика,
автор: bakzhanar05
Предмет: Английский язык,
автор: anzhelika2008l
Предмет: Математика,
автор: Лайстор
Предмет: Обществознание,
автор: sofiaiana